Mucosa-Associated Invariant T Cells Are Systemically Depleted in Simian Immunodeficiency Virus-Infected Rhesus Macaques - Vinton, Carol (J Virol, 2016)
Mucosa-associated invariant T (MAIT) cells contribute to host immune protection against a wide range of potential pathogens via the recognition of bacterial metabolites presented by the major histocompatibility complex class I-related molecule MR1. Although bacterial products translocate systemically in human immunodeficiency virus (HIV)-infected individuals and simian immunodeficiency virus (SIV)-infected Asian macaques, several studies have shown that MAIT cell frequencies actually decrease in peripheral blood during the course of HIV/SIV disease. However, the mechanisms underlying this proportional decline remain unclear. In this study, we characterized the phenotype, activation status, functionality, distribution, and clonotypic structure of MAIT cell populations in the peripheral blood, liver, mesenteric lymph nodes (MLNs), jejunum, and bronchoalveolar lavage (BAL) fluid of healthy and SIV-infected rhesus macaques (RMs). Low frequencies of MAIT cells were observed in the peripheral blood, MLNs, and BAL fluid of SIV-infected RMs. These numerical changes were coupled with increased proliferation and a highly public T cell receptor alpha (TCRα) repertoire in the MAIT cell compartment without redistribution to other anatomical sites. Collectively, our data show systemically decreased frequencies of MAIT cells likely attributable to enhanced turnover in SIV-infected RMs. This process may impair protective immunity against certain opportunistic infections with progression to AIDS. IMPORTANCE The data presented in this study reveal for the first time that MAIT cells are systemically depleted in an AIDS virus infection. These findings provide a new mechanistic link with our current understanding of HIV/SIV pathogenesis and implicate MAIT cell depletion in the disease process.